Examining the spiral of silence in offline and online expression of public opinion on recruitment of women into the Kuwaiti military - Alkandari, Ali; Frederick, Edward; Alsaber, Ahmad R.; Alhashem, Fatimah (Frontiers in Sociology, 2025)
This study used the Spiral of Silence (SOS) and Uses and Gratifications (U&G) framework to examine the influence of religion on offline and online expressions of opinion about women in the Kuwaiti military. A self-administered questionnaire was completed by 652 university students in Kuwait. Data were analyzed using Multiple Linear Regression (MLR) to identify predictors of opinion expression in offline and online settings. Predictor variables included fear of social isolation, internally and externally driven religious fears, religiosity, and media use behaviors. Our results revealed culturally oriented factors, including fear of social isolation and externally driven religious fear, predicted avoidance of expressing opinions in offline contexts. On the other hand, personality-oriented factors, including personal religious inclinations, “social use of religious media,” and frequency of occasions spent using the X platform, triggered the expression of opinion on the topic in the online context. The results are discussed in terms of the influence of online media in an Arab and Muslim culture. The influence of online media can have a liberating effect in a “solid” and “static” religious public opinion climate. This study suggests that when online discussions regarding women issues are circulated offline by people, the discussions can have transformative effects on the restrictive culture.